PERBANDINGAN LATIHAN BOOMERANG RUN DAN HEXAGON DRILL TERHADAP FOOTWORK ATLET BULUTANGKIS - Susanto, Rivaldy Adiska Susanto; Dinar Dinagsit; Anin Rukmana (UNIB Press, 2025)
This study uses a quantitative approach with an experimental design to analyze the effect of Boomerang Run and Hexagon Drill training on badminton athletes' footwork. The research sample consisted of 30 athletes of the UPI Sumedang Campus Badminton UKM who were selected by purposive sampling based on certain criteria. The instrument used was a footwork skill test that had a validity of 0.865 and a reliability of 0.758. Data were analyzed using a normality test (Shapiro-Wilk), a homogeneity test (Levene's Test), a hypothesis test (Independent Samples T-Test), and a correlation test (r test) with the SPSS 26.0 program. The results showed that the Sig. (2-tailed) value was 0.000 <0.05, so it can be concluded that Boomerang Run and Hexagon Drill training had a significant effect on improving badminton athletes' footwork. In addition, the R-Square test results showed that Boomerang Run training had an effect of 68.2% on improving footwork, while Hexagon Drill had an effect of 48.2%. Thus, this study confirms that both training methods are effective in improving badminton athletes' footwork, with Boomerang Run having a greater impact.